Pemanfaatan Limbah Pertanian sebagai Bahan Dasar Pembuatan Pakan Bebek di Desa Kandangmukti, Kecamatan Leles, Garut - Alamsyah, Femi Fauziah; Rizky Muhammad Fauzan; Cahnia Cendi Aulia Muslim; Shendi Hendrawan; Najwan Muttaqin; Siti Arfi Mutoharoh; Fooza Hasna Madani; Siti Fatimah; Nadila Suci Nugraha; Sheryl Shabirah Nail; Naufal Fawwaz Mudzaffar (Yayasan Cendekia Gagayunan Indonesia, 2024)
Agricultural waste, particularly rice husk, is often burned or discarded, resulting in lost potential value and underutilization. Rice husk, a byproduct of rice milling, contains nutrients that can enhance soil fertility if managed properly. However, the common practice of burning leads to nutrient loss. This study aims to convert rice husk into poultry feed for ducks by mixing it with other ingredients such as leaves and bran. This approach not only utilizes agricultural waste but also reduces feed production costs, which typically represent 70% of farmers' expenses. The research involved several steps: waste collection, feed preparation, feeding trials with ducks, and analysis of the results. The findings show that ducks fed with the processed agricultural waste gained significantly more weight compared to those on commercial feed. This method effectively turns agricultural waste into valuable livestock feed, reducing waste in landfills and mitigating environmental pollution.